Prevalence of human papillomavirus in Wenzhou, China: a cross-sectional study of 127 938 outpatient women - Gang Chen; Hong Huang; Mengqi Zhang; Xuchao Dai; Zhigang Wu; Yuanyuan Zheng (BMJ Open, 2022)
Objectives Understanding the prevalence and genotype distribution of human papillomavirus (HPV) is critical for managing HPV vaccination programmes. Using a retrospective cross-sectional study, we examined long-term trends of HPV prevalence in Wenzhou, a coastal city in China.Setting and participants Cervical exfoliated cells were collected from 127 938 women who underwent cervical cancer screening at the gynaecology outpatient clinic of Wenzhou People’s Hospital from January 2011 to December 2020. HPV infections and genotypes were determined. The HPV genotypes were 16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68, 6, 11, 42, 43, 44 and 81. From 2011 to 2014, we used PCR and inflow hybridisation for typing assays. In 2015–2020, HPV genotyping was performed on the collected specimens using PCR and flow fluorescence hybridisation.Results The overall prevalence of HPV infection was 17.8%. Across age groups, the prevalence fluctuated between 15.9% and 37.4%, with two peaks in the ≤20 and ≥51 year groups. The annual prevalence varied between 12.2% and 28.8%, with a significant decrease in 2011–2018 and a flat trend in 2018–2020. The five most common HPV genotypes were HPV52 (3.6%), 16 (3.0%), 58 (2.5%), 53 (1.9%) and 81 (1.3%). The prevalence of high-risk gene subtypes HPV56, 59 and the low-risk subtype HPV44 increased. Single HPV infection was the most common.Conclusion The prevalence of HPV in Wenzhou is low to mid-range; however, the high-risk genetic subtypes HPV56 and 59 have increased in recent years. We need to promote HPV vaccination and increase education regarding safer sex.